2007
DOI: 10.1177/0145721707304170
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Promotoras on Social Support and Glycemic Control Among Members of a Farmworker Community on the US-Mexico Border

Abstract: These findings document improvement in both clinical and social health indicators for Mexican Americans in a farmworker community when a promotora model is used to provide and facilitate culturally relevant support for diabetes self-management practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 15 publications
1
85
2
1
Order By: Relevance
“…Implementation through communitybased organizations, however, does not preclude linkage of PS with clinical care. One promotora program among migrant farm workers was successful in developing linkages with a local community health center to enhance clinical services for participants (57). Reciprocally, in PS programs implemented through health care settings, supporters may provide natural linkages from those settings to the communities they serve.…”
Section: Organizational Issuesmentioning
confidence: 99%
“…Implementation through communitybased organizations, however, does not preclude linkage of PS with clinical care. One promotora program among migrant farm workers was successful in developing linkages with a local community health center to enhance clinical services for participants (57). Reciprocally, in PS programs implemented through health care settings, supporters may provide natural linkages from those settings to the communities they serve.…”
Section: Organizational Issuesmentioning
confidence: 99%
“…The patient navigation component of the study helped ensure that patients and their families were made aware of and are put in contact with community structures, facilities, and programming in a practical and useful manner. The present study is one of the first to show the efficacy of using CHWs to implement successful active living and healthy eating interventions among a pediatric population as well as adding to growing literature that demonstrates the effective use of CHWs among persons living in low income communities to promote health and disease management strategies [18]- [20]. Our study is subject to the limitations of participants serving as their own controls; hence issues of self-selection and generalizability may exist.…”
Section: Discussionmentioning
confidence: 93%
“…A randomized, controlled intervention among 150 Mexican-American adults with diabetes living along the U.S.-Mexico border found that promotora-taught classes were effective in improving glycemic control (hemoglobin A1C) 6 months postintervention compared to a control group that received standard clinic care only (Lujan et al 2007). A demonstration project in a similar population reported greater improvement in glycemic control among those patients who participated more frequently in promotora-led support groups (Ingram et al 2007).…”
Section: Implications For the Futurementioning
confidence: 99%